'A battlefield for public opinion struggle': how does news consumption from different sources on social media influence government satisfaction in China?. Issue 4 (12th March 2021) - Zhang, Yiyan; Guo, Lei
ABSTRACT: While the political influence of the Internet, especially social media, on people's attitude toward their governments has been widely discussed in western democracies, the situation in authoritarian regimes such as China has not yet been adequately addressed. The current Chinese administration considers social media 'the main battlefield for public opinion struggle' between the official discourse and those challenging it. To provide clues about who is shaping the public opinion, this study examined how consuming news from competing information sources on social media influences Chinese citizens' satisfaction with the central and local government. Based on a nationally representative survey of 2, 882 Chinese adults, the study found that consuming news from governmental sources on the country's major social media platforms – Weibo and WeChat – was positively associated with citizens' satisfaction with the central government, while exposure to alternative news sources on WeChat had a negative impact on both central and local government satisfaction. Additionally, news consumption from mainstream media sources on social media did not significantly influence the public's government satisfaction. This paper contributes to the current literature by revealing that social media do not provide a unified agenda and by emphasizing the impact of platform affordances on people's political attitudes.